Spatiotemporal Pattern Evolution in Global Green Trade Networks: Implications for Health Economics - Haiyan Zhou; Shaobin Wei; Xun Xi; Haitao Zhou; Hao Hu (Discrete Dynamics in Nature and Society)
Big health industry is an industry that provides whole process and all factor products and services for human comprehensive physical and mental health. With the increasingly close relationship between health and environment, green products take into account the characteristics of environmental protection, resource intensification, safety, and health, so that the green product industry for the purpose of health and environmental protection has become an important branch of the big health industry. To give a clear portrayal of changes in the global green product trade system, this study derives relevant trade data from the World Bank and the UN Comtrade and by analyzing the spatiotemporal evolution characteristics of the global green product trade pattern from 2001 to 2018, and it explores the product structure and status changes of countries (regions) in the global trading system for green products. According to the research findings, the closely connected global trade network for green products continues to expand. This is a typical network comprising “smaller worlds”; the focus of green product exports has largely stayed unchanged, while imports are shifting from North America and East Asia towards North America, Europe, and the Middle East; the spatial structure of the network shows a transition away from the original transcontinental “dual arch” pattern with the United States at the core towards a “transcontinental + intracontinental” one characterized by the coexistence of “multiple arches” centering around Europe and Asia; the trade network adopts a “point-to-point” model, with no obvious interdependence and competition between countries (regions); furthermore, geographically proximate and culturally similar countries are prone to have closer trade ties. By clarifying the global trade network of green products industry under the background of big health industry, it will help to deepen the understanding of the relationship between participating countries, promote the long-term and stable development of national health industry trade, provide the public with more safe and harmless products, better meet the global public’s health needs, and effectively enhance the sustainability of public health.